(untitled) (The Journal of Plant Protection Sciences, 2021)
Kalimpong hills in Darjeeling district endowed forewarning or prediction system by with sub-tropical climate, is congenial for monitoring or predicting the pest population rearing of bivoltine silkworm superior in (10). It is being widely used in the agricultural quality in comparison to hybrids reared in production system now-a-days as a tool for plains of West Bengal. Bivoltine silkworms can lesser damage to natural enemy complex and be successfully reared during March-October also limits environmental pollution by way of when adequate rainfall and prevailing reduced pesticide application on requirement temperature facilitates production of adequate basis and apply when necessary strategy. The mulberry foliage.